2018
DOI: 10.3389/fimmu.2018.00380
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Prime-Boost Combinations Highlight the Crucial Role of Adjuvant in Priming the Immune System

Abstract: The induction and modulation of the immune response to vaccination can be rationally designed by combining different vaccine formulations for priming and boosting. Here, we investigated the impact of heterologous prime-boost approaches on the vaccine-specific cellular and humoral responses specific for a mycobacterial vaccine antigen. C57BL/6 mice were primed with the chimeric vaccine antigen H56 administered alone or with the CAF01 adjuvant, and boosted with H56 alone, or combined with CAF01 or with the squal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…While we observed only a moderate differential expression of T cell activation modules 7 days after boost, the immunological analysis performed 10 days after boosting showed a higher frequency of H56-specific CD4+ T cells and germinal center B cells in dLN, a strong H56-specific humoral response and a higher frequency of ASC in spleen of mice primed with H56 + CAF01. We and others have previously shown that the presence of the CAF01 adjuvant combined with the antigen in the vaccine formulation used for priming is crucial for the induction of the germinal center reaction, assessed by the presence of the T follicular and germinal center B cells ( 4 , 46 ), as well as for a strong T cell mediated immune response with a Th1 and Th17 profile ( 4 , 6 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…While we observed only a moderate differential expression of T cell activation modules 7 days after boost, the immunological analysis performed 10 days after boosting showed a higher frequency of H56-specific CD4+ T cells and germinal center B cells in dLN, a strong H56-specific humoral response and a higher frequency of ASC in spleen of mice primed with H56 + CAF01. We and others have previously shown that the presence of the CAF01 adjuvant combined with the antigen in the vaccine formulation used for priming is crucial for the induction of the germinal center reaction, assessed by the presence of the T follicular and germinal center B cells ( 4 , 46 ), as well as for a strong T cell mediated immune response with a Th1 and Th17 profile ( 4 , 6 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…The chimeric antigen H56, a promising vaccine candidate against Mycobacterium tuberculosis was used as model vaccine antigen, and administered by the parenteral route alone or combined with the CAF01 adjuvant, a liposome system capable to elicit both humoral and cellular responses . Boosting was performed with a lower dose of antigen alone, according to an immunization schedule already tested . The analysis was aimed to identify, in an automated and unbiased way, different B cell subtypes elicited by booster immunization and determine their frequency among mice primed with or without the adjuvant component.…”
mentioning
confidence: 99%
“…FlowSOM is considered one of the best high‐performance algorithms in automated identification of cell subsets showing an extremely fast runtime . It has also been used for characterizing both the cell phenotype and the cellular functionality, such as the simultaneous production of intracellular cytokine and degranulation . The FlowSOM algorithm is based on a self‐organizing map (SOM), where similar cells are assigned to the same node.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Automated analysis can be particularly efficient also for identifying polyfunctional antigen-specific T cells elicited by vaccine administration or natural infection. Different computational tools, ranging from the Boolean combination gates, FlowSOM, or integrated approach combining targeted feature extraction (OpenCyto) with dimension reduction (t-SNE) have indeed been used to profile the polyfunctional activity of tuberculosis antigen-specific T cells and visualize treatment-specific differences between different vaccine formulations [106][107][108]. These studies demonstrate the importance of automated approaches to identify and visualize changes in very rare, multifunctional, antigen-specific T cells across different conditions, in flow cytometry datasets.…”
Section: Flow Cytometry In Vaccine Studies and The Advantages Of Compmentioning
confidence: 99%